2020
DOI: 10.1016/j.earlhumdev.2020.105213
|View full text |Cite|
|
Sign up to set email alerts
|

Withdrawn: Vaccine hesitancy among Maltese Healthcare workers toward influenza and novel COVID-19 vaccination

Abstract: Introduction Vaccine hesitancy is a chronic public health threat. This study was carried out to ascertain Maltese healthcare workers' hesitancy to a novel COVID-19 vaccine and correlate this with influenza vaccine uptake. Methods A short, anonymous questionnaire was sent out to all of Malta's government sector healthcare workers via the service's standard email services (11–19/09/2020). A total of 9681 questionnaires were posted electronically, with 10.4% response. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
112
4
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(132 citation statements)
references
References 30 publications
(22 reference statements)
11
112
4
3
Order By: Relevance
“…The results in Italy and France can be viewed from the perspective of lacking confidence in the safety of these vaccines, since such a negative attitude was reported previously in these countries [ 27 ]. In addition, low rates of COVID-19 vaccine acceptance were reported among students and healthcare workers in Malta—44.2% and 52.0%, respectively [ 73 , 74 ]. Variable results were also reported in other European countries with rates as high as 80.0% in Denmark, and as low as 56.3% in Poland [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results in Italy and France can be viewed from the perspective of lacking confidence in the safety of these vaccines, since such a negative attitude was reported previously in these countries [ 27 ]. In addition, low rates of COVID-19 vaccine acceptance were reported among students and healthcare workers in Malta—44.2% and 52.0%, respectively [ 73 , 74 ]. Variable results were also reported in other European countries with rates as high as 80.0% in Denmark, and as low as 56.3% in Poland [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly cited reasons for hesitation or refusal were fear of side effects [1,22,47,49,50], safety [5,34,37,51], and effectiveness [2,5,24,[52][53][54]. Belief that vaccines are unnecessary [43,50,52,55], inadequate information [34,47,50], unknown/short duration of immunity [2,5,50,53], and a general anti-vaccine stand [1,10,55] were associated with lower acceptance.…”
Section: Vaccine Attributes and Individual Factorsmentioning
confidence: 99%
“…Three international studies investigated healthcare professionals' attitudes and found similar concerns about vaccine safety and effectiveness and receptivity predictors including previous vaccination history, perceived risk or exposure, and being older, male, or a doctor [7,55,62]. Healthcare workers in Indonesia had greater acceptance than the public (OR: 1.57, 95% CI: 1.12-2.20) [63] while nurses in Hong Kong indicated low intention (40%) [7].…”
Section: Vaccine Attributes and Individual Factorsmentioning
confidence: 99%
“… 30 These negative attitudes seem to remain among HCP regarding COVID-19 vaccines. 15 Research suggests additional concerns among HCP specifically regarding: COVID-19 vaccines (including insufficient safety and efficacy data and long-term side effects) and breakdowns of trust between HCP and institutions (due to inadequate personal protective equipment [PPE] and concerns that getting vaccinated against COVID-19 will be linked to requirements to work with COVID-19 patients). 15–17 …”
Section: The Case For and Against Mandating Covid-19 Vaccination Of Hmentioning
confidence: 99%